Current Innovations In The Productions Of Biofuels From Lignocellulose Biomass As A Source Of Renewable Energy (International Journal of Food and Nutritional Sciences, 2022)
Biofuel is non-fossil fuel derived from renewable organic biomass like plant, animal, microbial, and human waste. Biofuel generates bioenergy. While energy demand rises, fossil fuel availability is finite and falling. To alleviate this shortfall, people must move from fossil fuels to biofuels, which efficiently fulfil present and future demand. This research focuses on second-generation lignocellulosic biofuels using non-edible plant biomass to reduce environmental impact (i.e., cellulose, lignin, hemicelluloses, non-food material). It's crucial to convert lignocellulosic feedstock before producing ethanol. However, it's crucial to remember that the generation of biofuel is currently not cost-effective due to a number of technological limitations, necessitating an upgrade in the techniques used. The cost-effectiveness of the process and the limits of the different technologies used are still issues with producing biofuel. Due to this, there is a critical need for continued, improved research and development to guarantee that lignocellulosic biofuel is available on the market.